2020
DOI: 10.1371/journal.pone.0229053
|View full text |Cite
|
Sign up to set email alerts
|

Conventional dose rate spatially-fractionated radiation therapy (SFRT) treatment response and its association with dosimetric parameters—A preclinical study in a Fischer 344 rat model

Abstract: To identify key dosimetric parameters that have close associations with tumor treatment response and body weight change in SFRT treatments with a large range of spatial-fractionation scale at dose rates of several Gy/min. Methods Six study arms using uniform tumor radiation, half-tumor radiation, 2mm beam array radiation, 0.3mm minibeam radiation, and an untreated arm were used. All treatments were delivered on a 320kV x-ray irradiator. Forty-two female Fischer 344 rats with fibrosarcoma tumor allografts were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…PVDR is an important dosimetric parameter recommended in GRID therapy documentation as a measure of dose heterogeneity based on recent guidelines [ 27 , 29 ]. The determination and reporting of the dose heterogeneity is particularly important because preclinical data suggest that it is related to tumour response [ 30 , 31 ]. In 3D tumour volumes treated with GRID therapy, the computation and reporting of PVDR adds significant complexity to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…PVDR is an important dosimetric parameter recommended in GRID therapy documentation as a measure of dose heterogeneity based on recent guidelines [ 27 , 29 ]. The determination and reporting of the dose heterogeneity is particularly important because preclinical data suggest that it is related to tumour response [ 30 , 31 ]. In 3D tumour volumes treated with GRID therapy, the computation and reporting of PVDR adds significant complexity to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In all configurations (except Configuration #2 ), the increase in PVDR is related with an equivalent drop of the valley dose due to the larger separation between minibeams. This is a significant result because the valley dose and ctc distance seem to have a significant impact on healthy tissue tolerance in SFRT techniques [ 35 , 36 , 37 ]. Among the configurations investigated, the use of a magnetic field inside the water phantom, mimicking an MRI-guided machine, is the most effective approach to optimize the spatial modulation.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , the geometric dimensions of the multiple beams in preclinical SFRT are very small. Microbeams are the smallest (with a beam width of 100 µm or less) [ 3 , 15 ], whereas minibeams are the largest (with a beam width between 100 µm and 1 mm) [ 4 , 16 , 17 ]. Numerous preclinical SFRT studies have shown that normal tissue tolerates irradiation exceptionally well, even when the peak dose is 100 Gy or more in a single treatment [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbeams are the smallest (with a beam width of 100 µm or less) [ 3 , 15 ], whereas minibeams are the largest (with a beam width between 100 µm and 1 mm) [ 4 , 16 , 17 ]. Numerous preclinical SFRT studies have shown that normal tissue tolerates irradiation exceptionally well, even when the peak dose is 100 Gy or more in a single treatment [ 17 , 18 , 19 , 20 ]. The sparing of normal tissue in conjunction with the tumor ablation of preclinical SFRT has been shown to significantly prolong animal survival [ 6 , 15 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%